Technical feasibility of newborn screening for spinal muscular atrophy by next-generation DNA sequencing - Shum, Bennett O. V.; Henner, Ilya; Cairns, Anita; Pretorius, Carel; Wilgen, Urs; Barahona, Paulette; Ungerer, Jacobus P. J.; Bennett, Glenn (Frontiers in Genetics, 2023)
Newborn bloodspot screening (NBS) assays for spinal muscular atrophy (SMA) typically use a polymerase chain reaction (PCR) based assay to identify individuals with homozygous deletion in exon 7 of the SMN1 gene. Due to high DNA sequence homology between SMN1 and SMN2, it has previously been difficult to accurately bioinformatically map short reads from next-generation DNA sequencing (NGS) to SMN1, resulting in low analytical performance and preventing NGS being used for SMA screening. Advances in bioinformatics have allowed NGS to be used in diagnostic settings, but to date these assays have not reached the scale required for high volume population newborn screening and have not been performed on the dried blood spot samples that NBS programs currently use. Here we integrate an NGS assay using hybridisation-based capture with a customised bioinformatics algorithm and purpose designed high throughput reporting software into an existing NBS program to achieve a laboratory workflow for population SMA screening. We tested the NGS assay on over 2500 newborns born over 2 weeks in a NBS program and show high sensitivity and specificity. Our results suggest NGS may be an alternate method for SMA screening by NBS programs, providing a multiplex testing platform on which potentially hundreds of inherited conditions could be simultaneously tested.